An on-chip thin film photodetector for the quantification of DNA probes and targets in microarrays - Fixe, F. (Oxford University Press, 2004)
A flat microdevice which incorporates a thin-film amorphous silicon (a-Si:H) photodetector with an upper layer of functionalized SiO(2) is used to quantify the density of both immobilized and hybridized DNA oligonucleotides labeled with a fluorophore. The device is based on the photoconductivity of hydrogenated amorphous silicon in a coplanar electrode configuration. Excitation, with near UV/blue light, of a single-stranded DNA molecule tagged with the fluorophore 1-(3-(succinimidyloxycarbonyl)benzyl)-4-(5-(4-methoxyphenyl)oxazol-2-yl) pyridinium bromide (PyMPO), results in the emission of visible light. The emitted light is then converted into an electrical signal in the photodetector, thus allowing the optoelectronic detection of the DNA molecules. The detection limit of the present device is of the order of 1 × 10(12) molecules/cm(2) and is limited by the efficiency of the filtering of the excitation light. A surface density of 33.5 ± 4.0 pmol/cm(2) was measured for DNA covalently immobilized to the functionalized SiO(2) thin film and a surface density of 3.7 ± 1.5 pmol/cm(2) was measured for the complementary DNA hybridized to the bound DNA. The detection concept explored can enable on-chip electronic data acquisition, improving both the speed and the reliability of DNA microarrays.